Automatic Fuel Pricing Mechanisms with Price Smoothing : Design, Implementation, and Fiscal Implications - Coady, David (Technical Notes and Manuals; Technical Notes and Manuals ;, 2013)
Many developing and emerging countries do not fully pass-through increases in international fuel prices to domestic retail prices, with adverse consequences for fuel tax revenues and tax volatility. The adoption of an automatic fuel pricing mechanism can help to address this problem, and the incorporation of a price smoothing mechanism can ensure pass-through over the medium term but also avoid sharp increases (and decreases) in domestic prices. This technical note addresses the following issues: (i) the design of an automatic fuel pricing mechanism; (ii) the incorporation of domestic price smoothing and resulting tradeoffs; (iii) the transition from ad hoc pricing adjustments to an automatic mechanism; and (iv) policies to support this transition and the maintenance of an automatic mechanism. A standardized template for simulating and evaluating the implications of alternative pricing mechanisms for price and fiscal volatility is available on request.